2014
DOI: 10.1007/s10333-014-0473-8
|View full text |Cite
|
Sign up to set email alerts
|

Uptake efficiency of 15N-urea in flooded and aerobic rice fields under semi-arid conditions

Abstract: The sustainability of traditional rice (Oryza sativa L.) cultivation in many Asian countries is being questioned due to severe water shortage conditions, envisaging the need for development of water-saving rice production technologies. A 2-year-field study on a typic Haplustalf soil was conducted to compare traditional transplanted rice-maize system with water-saving aerobic rice-maize system, with an overall objective of investigating the fate of fertilizer nitrogen (N) using 15 N-labeled urea. Results from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Therefore, the low APR values that resulted in spring and fall show that soil N was able to contribute to the crop N requirement; and although APR values were similar among the N rates, the 150 lb/acre N rate was sufficient to help meet the crop N requirement. Kadiyala et al (2014) determined through a field study on rice (Oryza sativa) that the apparent N recovery decreased with increased rate of application N.…”
Section: Soil F E R T I L I T Y I N D I C E S a T Preplantmentioning
confidence: 99%
“…Therefore, the low APR values that resulted in spring and fall show that soil N was able to contribute to the crop N requirement; and although APR values were similar among the N rates, the 150 lb/acre N rate was sufficient to help meet the crop N requirement. Kadiyala et al (2014) determined through a field study on rice (Oryza sativa) that the apparent N recovery decreased with increased rate of application N.…”
Section: Soil F E R T I L I T Y I N D I C E S a T Preplantmentioning
confidence: 99%
“…The rates and contents of nitrogen derived from fertilizer (N dff ) in water, plant and soil were calculated by Eqs. 4-9, respectively [29,33,37]. The nitrogen fertilizer efficiency was acquired by Eq.…”
Section: Data Processing and Statistical Analysesmentioning
confidence: 99%
“…15 N is another existent form of element nitrogen apart from 14 N. It has nearly the same physical and chemical characteristics as 14 N. When the 15 N tracer was applied into a specific ecosystem, the amount and distribution of 15 N in different environmental media (e.g. atmosphere, plant, microorganism, water and soil) could be quantified by using an isotope ratio mass spectrometer (IRMS) [27][28][29][30][31]. Therefore, 15 N tracing technology was widely applied to reveal the nitrogen behavior in the environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies of the fate of 15 N fate applied to lowland rice, CF is largely reported as the irrigation regime which provides superior isotopic nitrogen efficiency in relation to alternative methods D ong et al, 2012;Fillery and Vlek, 1982; M. D. M. Kadiyala et al, 2015b;. The common factor between these studies was they took place on Alfisols and/or puddled soils.…”
Section: The Isotopic Efficiencymentioning
confidence: 99%